ASPECTE DE ORDIN GEOLOGIC ŞI GEOMORFOLOGIC ALE DEALULUI BILAG ŞI CULOARULUI OIEJDEA-ŞARD (PANGEEA, 2025)
Geological and geomorphological characteristics of Bilag Hill andOiejdea-Şard Coridor. Bilag Hill has a special position in the relief structure of the middlebasin of Mures river. He is board, on all sides, by large valleys, namely: Mureş corridor,Ampoiului corridor and Oiejdea-Sard corridor. Oiejdea-Sard and Ampoiului corridors arevery broad, which could not be dug by the small rivers that cross them. The explanation canbe given of Mures river trail, which took the route from Teiuş through the corridorOiejdea-Sard, then Ampoiului valley, reaching the current course in south of Alba Iulia.Changing course is due to an abstraction, between Mures and Tarnave in the village Mihalţ,then installed on the course Târnavei Mures. The old route, on the north, west and south ofBilag Hill, was abandoned, and now it is occupied by small streams and rivers with muchsmaller and a very large meadow.